Sustainable Mine Closure ⎯ Issues and Lessons Learnt - Kunanayagam, R (Mine Closure 2006: First International Seminar on Mine Closure, 2006)
Two tests of the long term sustainability of a mining operation are its environmental and social legacies. Even fifteen years ago most mine closure plans dealt primarily with the engineering aspects of site decommissioning and the technical aspects of environmental remediation. However, due to increasing standards and a commitment to sustainability made by a number of leading mining companies, the industry is fast adopting an integrated approach (social, environmental, engineering and financial) to closure. This approach defines the closure legacy of the mine and frames the entire planning process of the mine cycle. Accordingly, this paper looks at examples of recent mine closures in developing countries in order to identify the main issues facing companies at closure. It examines some key lessons learned from these experiences and, in particular, the social and human relations aspects of closure.